The Kekuatan Adaptasi: Eksplorasi Praktik Resiliensi oleh Wirausaha Perempuan di Lingkungan Industri Kreatif Indonesia - Pratama, Aditya (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2024)
In densely populated Indonesia, startup growth is relatively low compared to neighboring countries such as Singapore, Thailand and Malaysia. Based on the 2021 MSME Online Data System (ODS), the number of female entrepreneurs is 86,325 (47.99%) and the number of male entrepreneurs is 93,574 (52.01%). In fact, many women in the business world can contribute to the progress of a country, especially by driving the economy. Based on the results of the research conducted, it can be concluded that women entrepreneurs have moderate resilience. This means that women entrepreneurs have reasonable abilities to overcome and adapt to serious events and problems in life. The aim of this research is to determine the resilience of women entrepreneurs in everyday life and in the male-dominated business world. The subjects of this survey were 50 female entrepreneurs. The data collection method in this research used the Reivich & Shatte Resilience Quotient Test Scale (RQ test). The data analysis technique used is descriptive statistics. The expected test results use a normality test with a normal distribution. The homogeneity test shows the results of a normal population distribution. The results of the one-sample t-test show that the hypothesis that women entrepreneurs have a certain level of resilience is accepted. Key Words : Entrepreneur, Resiliensi, Womenpreneur.